(3TQM eKdK GHf eGdcs - (3YHO Gddg GdYJjb Hf Pi GdNdGdi GdjYbhHis
(3ChdgG (B:s
(3fMeOc Gddg Ydi eG YdeJfG ef GddZi s
(3BNQgG (B:s
(3HGH eG Chdg aGA ef GdeKdK GdeNJda GdeYGfi (B: (3VQH GdjSGQ hJbGSe GdLRQ hGdVQH HGdbOGM hai GdMOjK Ef gPG GdOjf jSQ , Ci egd , hbO jSQ , jjSQ hCjSQ (B: (3ESJZfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eQbeIs
(3eUMMI s
(3cJHJ HYV YHGQJgG HGdMeQI hGdUaQI s
(3hYdjgG Jedc HGSe eMeO aGd Hf CMejO s
Keywords: (3GddZIs